Intravoxel Incoherent Motion Protocol Evaluation and Data Quality in Normal and Malignant Liver Tissue and Comparison to the Literature. Issue 2 (February 2016) - ter Voert, Edwin E.G.W.; Delso, Gaspar; Porto, Miguel; Huellner, Martin; Veit-Haibach, Patrick
Abstract : Objectives: Although intravoxel incoherent motion (IVIM) becomes more and more popular, there is currently no clear consensus on the number and distribution of b -values to use. In this work, we (1) tested and evaluated the data quality of a 25– b -value IVIM protocol in patients with malignant liver lesions and normal liver tissue as a standard of reference, (2) calculated an optimal b -value distribution and compared with the standard of reference, and (3) compared the 25– b -value protocol with other proposed protocols in the literature. Materials and Methods: Intravoxel incoherent motion imaging with 25 b -values was performed at 3 T in a total of 15 patients with malignant liver lesions. Reference IVIM parameter maps were calculated in tumor and normal liver tissue. With these parameters, optimal IVIM protocols with reduced numbers of b -values were calculated. These optimal IVIM protocols were again applied to calculate new IVIM parameter maps that were compared with the reference parameter maps by calculating mean relative errors. In addition, 35 other IVIM protocols, as found in literature, were compared in a similar way with the 25– b -value protocol serving as a standard of reference. Results: The mean relative error depends on the number of b -values and their distribution. In tumor tissue, the error is higher and more variable than in normal-appearing liver tissue. The largest errors occur in tumor tissue and in the protocols having low numbers of b -values in the IVIM protocols. In the calculated optimal IVIM protocols, the mean relative errors decreased by 40% or more when the number of b -values included increased from 4 to 16. The mean relative errors in the protocols adapted from the literature vary substantially between the various b -value distributions. One optimized 16– b -value protocol, which was found in literature, reduced the average relative error by 80% when compared with 4– and 5– b -value protocols listed in literature. Conclusions: Including more b -values and applying an optimized b -value distribution significantly reduces errors in the IVIM parameter estimates, thereby increasing its accuracy. This effect is even more pronounced in inhomogeneous tumor compared with that in normal liver tissue. However, when restrictions in acquisition time or patient-related factors apply, a minimum of 16 b -values should be considered for reliable results. Abstract : Supplemental digital content is available in the text.